Means of Modality in Linguistics as a Universal Linguistic Event - Mamatqulova Marhabo (International Journal on Integrated Education, 2022)
This article is devoted to the analysis of modal verbs and modal words in speech, semantic features, similarities and differences between them, their use in speech, grammatical analysis of modal verbs in English and modality Dedicated to collecting the studied sources in the category, identifying contradictions in them, finding shortcomings and filling them.